CHARACTER EDUCATION IN HADITH PERSPECTIVE: A STUDY ON STRENGTHENING MORAL VALUES IN CONTEMPORARY EDUCATION SYSTEM - Fatmal, Abd. Bashir; Imawati,; La Ode Ismail Ahmad,; Amin, Muhammadiyah (Jurnal Diskursus Islam, 2025)
Character education has become an important issue in the global education system, especially in the modern era characterized by rapid social, technological, and cultural changes. This study aims to explore the integration of moral values derived from the hadith of Prophet Muhammad in strengthening character education in the contemporary education system. A qualitative research method was used with a literature study approach and content analysis of hadiths related to character education, such as honesty, justice, empathy, responsibility, and humility. The results showed that hadith as the second source of Islamic teachings after the Qur'an, contains universal values that are relevant to forming noble individual characters. These values include honesty, compassion, justice, patience, and care for the environment, all of which can be integrated in the modern education curriculum. This research confirms that hadith-based character education is able to answer the challenges of moral degradation in the era of globalization, while offering practical solutions in building a young generation with integrity, social responsibility, and noble character. The implications of this research include the development of a hadith-based character education model, increasing the capacity of educators in teaching moral values, and collaboration between schools, families, and communities in strengthening character education. The integration of values from the hadith into the contemporary education system is a strategic step in creating a harmonious, just and civilized society.